(untitled) (ModaPalavra e-periódico, 2010)
The luxury brands are constructed and developed strategically for the maintenance and spreading of its values and personality. For the consolidation of the brand, the companies need to search a dif erential, with strategical actions that create the recognition of an only identity in the mind of the consumer. She enters the strategies of the brand, is the intense spreading of its logotipo in all its communication. This spreading to be carried through adequately and with ef ective results needs the aid of design graphical. This article looks for to present the use of the logotipos for the brands of luxury and the participation of design graphical, through the creation and management of brands (branding). Mainly in what the visual form says respect, the luxury brands are if using of `logos’ to reach the imaginary one of the people.